UNJUK KERJA PERALATAN PENYULINGAN AIR LAUT DENGAN PENAMBAHAN BATU KERIKIL PADA BASIN BERBAHAN BETON - Ladi, Jovan; Monintja, Nita C V; Lempoy, Kennie (Jurnal Poros Teknik Mesin UNSRAT, 2024)
Clean water is very important in human life. Clean water is a basic need that cannot be separated from the development of human life. In their daily life, humans are very dependent on clean water, its use in the long term makes clean water very difficult to obtain. The scarcity of clean water that is used by the people on a daily basis is also influenced by the factor of contamination of clean water by factory wastes. Clean water is currently something that is difficult for humans to obtain, this makes clean water production very expensive. This research was conducted to produce clean water using a distillation process. Seawater distillation is a process of purifying seawater from its existing content, namely salt. This process is a separation method by heating seawater to produce water vapor, which is then condensed to produce clean water. The seawater distillation process is a physical separation process between water and salt content by evaporating seawater, which then undergoes a condensation process. The process that will be used in this study is the process of adding gravel as an absorber to the production of clean water in the distillation apparatus to be studied. Based on the results of the analysis and discussion, it was found that with the addition of gravel the solar radiation would increase and the production of water condensation would also increase. Keywords : Distillation, Absorber, Concrete, Gravel.